2014
DOI: 10.2174/1874155x01408010340
|View full text |Cite
|
Sign up to set email alerts
|

Research on Urban Rail Train Passenger Door System Fault Diagnosis Using PCA and Rough Set

Abstract: Train passenger door is the key system for operation and maintenance of urban rail train. In this paper, working process of the passenger door system of urban rail train is analyzed and the mathematical model is established. Firstly, the method of parameter estimation is used to obtain physical parameters of doors in different working conditions. Then fault diagnosis experiment is carried out on train passenger door with principal component analysis and rough set theory. In the end, fault diagnosed accuracies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 10 publications
(4 reference statements)
0
4
0
Order By: Relevance
“…The abnormality will not affect the train running in continuous mode. Under the formula, the abnormality becomes a dominant fault [45]. By monitoring such abnormal signs, it is possible to regularly check the running status of the backup system equipment, and find the fault of the backup system equipment in time.…”
Section: Results and Analysismentioning
confidence: 99%
“…The abnormality will not affect the train running in continuous mode. Under the formula, the abnormality becomes a dominant fault [45]. By monitoring such abnormal signs, it is possible to regularly check the running status of the backup system equipment, and find the fault of the backup system equipment in time.…”
Section: Results and Analysismentioning
confidence: 99%
“…Despite rigorous maintenance schedules, doors and brakes continue causing incidents which drive undesirable consequences, and in addition, the causes of failure cannot always be identified. Doors, in particular, have been a subject of research to find better ways to identify and prevent failure (Dinmohammadi et al, 2016;Van der Gucht et al, 2011;Shuai et al, 2014;Cheng et al, 2013). A case study conducted in UK reported that the cause of failure could not be identified for 42% of a total of 205 incidents with the passenger doors (Dinmohammadi et al, 2016).…”
Section: Performance Of Rail Passenger Doors and Brakes Systemsmentioning
confidence: 99%
“…Presently, a variety of state recognition methods have been developed in the field of fault state recognition, mainly divided into methods that are based on qualitative empirical knowledge, methods based on analytical models and methods based on data-driven. Lin S. [6] used principal component analysis (PCA) and rough set-based fault identification method for train door fault identification. The comparison found that, although the PCA method can determine whether a fault has occurred, it cannot perform fault identification.…”
Section: Introductionmentioning
confidence: 99%